PERANCANGAN SISTEM INFORMASI INTEGRASI APLIKASI POINT OF SALE MINI MARKET - Sandy Kosasi (Teknik Informatika Universitas Malikussaleh, 2019)
Point of sale application integration system design can give better service to theconsumer and potential customer, example in the price count and sum of itempurchased can become faster, acurate and quantity of the items no longer rely on themanual recording. Information about recording sales transaction becomes more complete and more varieties according to the needed report. As for the research purposeis create integrated information point of sale application system between business process to the warehouse, sales and cashier. Experiment is using case study with research and development method and technique to gather data are observation, interview and question list. This application integration system design is using waterfall approach and the design is using use case diagram, activity, sequence andclass. The research instrument consist of cashier application (front office), warehouse application module and report application module that needed. Application informationintegration system consists of module like sales management, sales data edit, equipmentdata insertion, pricing of the goods and report creation.